Hubungan Health Anxiety dan Cyberchondria: Sebuah Tinjauan Literatur Naratif - Putu Angita Gayatri; Ariana, Atika Dian (Universitas Airlangga, 2024)
Cyberchondria is defined as excessive or repeated search for health-related information on the internet that results in distress and/or anxiety. However, it remains unclear whether health anxiety triggers excessive search for health information on the Internet and whether such anxiety arises after excessive searches. A narrative literature review was conducted to summarize and analyze research related to health anxiety and cyberchondria. The results revealed a moderate to high relationship between health anxiety and cyberchondria. However, this reciprocal relationship could not be found in the subsample of clinically anxious individuals. Thus, cyberchondria may also be explained as a phenomenon that may appear in individuals with non-clinical levels of health anxiety, rather than as a characteristic of clinically health anxious individuals. Therefore, further empirical research is required to explore the relationship and influence of health anxiety on cyberchondria in more specific samples.